Screening, Diagnosis, and Treatment of Pediatric Ocular Diseases - Matthew Lam; Donny Suh (MDPI AG, 2022)
Vision is an important aspect of a child's quality of life and intellectual, social, and emotional development. Disruptions to vision during infancy and early childhood can cause lifelong vision impairment or blindness. However, early identification and treatment of eye disease can prevent loss of sight and its consequent long-term effects. Therefore, screening guidelines exist to guide physicians in detecting the most common threats to sight in the different stages of infancy and childhood. This review describes common causes of pediatric vision impairment, the recommended screening guidelines for diagnosing them, and current treatment modalities.